Plasticiser transportation studies in NR and acrylonitrile-butadiene rubber 1. Diffusion coefficient and equilibrium uptake of TBEP in NBR vulcanisates - Faridah H A H; Farid A S; Tinker A J (Journal of Rubber Research, 2004)
The diffusion coefficients (D) of tributoxyethylphosphate in gum, white- and black-filled vulcanisates of acrylonitrile-butadiene rubber (NBR) determined by means of mass uptake measurements were observed to decrease as crosslink density increases. As filler level increases for black-filled vulcanisates of NBR at fixed sulphur and accelerator levels, D was observed to continuously decrease. D, on the other hand, was found to increase as filler level increases in white-filled vulcanisates of NBR at fixed sulphur and accelerator levels. These observations are explained in terms of degree of rubber-filled interaction.
Keywords: Absorption; Black-filled; Crosslink density; Diffusion coefficient; Gum; NBR; Plasticiser; TBEP; Vulcanisates; White-filled